PEMBUATAN BUSANA PESTA MENGGUNAKAN KOMBINASI KAIN SHIBORI DENGAN VARIASI SULAMAN PITA JEPANG - Arina Haq; Aldhis Safitry (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Shibori fabrics is one of the kind materials which has its own circlenes especially in its uniqe and ethnic design, it's light but it looks elegant.This research will innovate to shibori fabrics which will be cultivated become party clothing, to beautify party clothing performance which is made, the writter applied one of the ornaments that is